Hydrologic connectivity and threshold behavior of hillslopes with fragipans and soil pipe networks. Issue 13 (18th May 2017) - Wilson, G.V.; Nieber, J.L.; Fox, G.A.; Dabney, S.M.; Ursic, M.; Rigby, J.R.
Abstract: Many concepts have been proposed to explain hydrologic connectivity of hillslopes with streams. Hydrologic connectivity is most often defined by qualitative assessment of spatial patterns in perched water tables or soil moisture on hillslopes without a direct linkage to water flow from hillslopes to streams. This form of hydrologic connectivity may not explain the hydrologic response of catchments that have network(s) of preferential flow paths, for example, soil pipes, which can provide intrinsic connectivity between hillslopes and streams. Duplex soils are known for developing perched water tables on hillslopes and fostering lateral flows, but the connectivity of localized perched water tables on hillslopes with soil pipes has not been fully established. The objectives of this study were to characterize pipeflow dynamics during storm events, the relationships between perched water tables on hillslopes and pipeflows, and their threshold behaviour. Two well‐characterized catchments in loess soil with a fragipan were selected for study because they contain multiple, laterally extensive (over 100 m) soil pipe networks. Hillslopes were instrumented with shallow wells adjacent to the soil pipes, and the wells and pipe collapse features were equipped with pressure transducers. Perched water tables developed on hillslopes during a wetting up period (October–December) and became well connected spatially across hillslope positions throughout the high flow period (January–March). The water table was not spatially connected on hillslopes during the drying out (April–June) and low flow (July–September) periods. Even when perched water tables were not well‐connected, water flowing through soil pipes provided hydrologic connectivity between upper hillslopes and catchment outlets. Correlations between soil pipeflow and perched water tables depended on the size and location of soil pipes. The threshold relationship between available soil‐moisture index plus storm precipitation and pipeflow was dependent on the season and strongest during dry periods and not high‐flow seasons. This study demonstrated that soil pipes serve as a catchment backbone of preferential flow paths that provide intrinsic connectivity between upper hillslopes and streams.